Current topics of interdisciplinary cooperation between engineering and human sciences - Angela Dressler; Nina Gerber; Angela Menig; Otilia Pasnicu; Alina Stöver; Joachim Vogt (Zeitschrift für Arbeitswissenschaft, 2023)
In this article, we highlight current research directions in the Technikpsychologie research area, using the example of the interdisciplinary research work of FAI (Work and Engineering Psychology Research Group at the Technical University of Darmstadt) and the articles included in this special issue. To this end, we relate the articles in this special issue from the research areas of road traffic planning (Hupfer et al.), usable IT security and privacy solutions (Renaud), social aspects of technically mediated communication (Diefenbach), human-centered interface design (Mucha et~al.), aviation safety (Santel), human-centered design of autonomous vehicles (Lindner & Stoll), and perceptual psychology-oriented product design (Zandi & Khanh) to current research projects at FAI. Practical Relevance Technical products only offer added value by efficiently supporting users in achieving their goals if they have been developed appropriately for the context of use and the individual characteristics of the users. The human-centered design of—especially technical—products reflects this through an iterative and participatory development process. In this article, we describe nine examples of such human-centered design of technology products. The research results and the methods presented provide insights for developers and decision-makers in the fields of transportation, IT, vehicle development and general product design.
Keywords: 650; Technikpsychologie; Engineering Psychology; Human-Machine-Interaction; Ingenieurpsychologie; Mensch-Maschine-Interaktion